Effectiveness Of Using ECDIS Learning Media Software For Computer Based Learning - Arif Rakhman Suharso (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The use of computers in the development of Electronic Chart Display and Information System (ECDIS) teaching materials can be used to assist lecturers in learning activities on vocational campuses as well as other materials in the Computer Base Training (CBT) laboratory at the Indonesian Maritime Polytechnic. The CBT laboratory provides learning materials on ship machinery systems and multiple choice questions for learning evaluation. The purpose of this study was to determine the level of effectiveness of the use of ECDIS material learning media software when used computer-based. The method used in this study is a qualitative method by looking at the final grades of students. This software consists of 42 slides of ECDIS material theory, 1 slide of ECDIS material video tutorial, 1 slide of ECDIS material practice, 20 slides of multiple choice evaluation questions, and 1 slide of final grades made using Visual Basic software. The results of the test showed that all cadets who attended the lecture were successful in using the software until the final grade was obtained.